Comparison of the characteristics of the chiral analog of the de Vries type of smectic-A* phase - VIJ, JAGDISH KUMAR; PANARIN, YURI PETROVICH (The American Physical Society, 2003)
In this paper we compare the results of three ferroelectric materials that exhibit unusual smectic-A (SmA) phases. These phases have been assigned to chiral analogs of the de Vries SmA phase. Several experimental techniques have been employed for this investigation. The possible molecular structures of de Vries SmA* phases are discussed.
PUBLISHED
Keywords: Electronic & Electrical Engineering